ANALISIS KESALAHAN KONSEP DALAM MENJAWAB SOAL-SOAL PADA MATERI KESEBANGUNAN MENGGUNAKAN CERTAINTY OF RESPONSE INDEX - Hamzah, Evandry; Yani T, Ahmad; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to determine and describe concept mistakes of students in answering questions on congruence material using the Certainty of Response Index (CRI). The method used is descriptive method. The research was conducted in SMA Negeri 9 Pontianak. Based on the results of the analysis using the CRI students experienced concept mistakes with an average of 53.34%. Mistakes when restating the concept of congruence have been studied as many as 18 students (50%). Students with high confidence incorrectly choose the right statement related to the concept of congruence. Mistakes when classifying objects based on whether or not fulfilled the requirements that form the concept of congruence as many as 21 students (58.33%). Students with high confidence incorrectly determine the congruent flat shape. Mistakes when applying the concept of congruence logically are 20 students (55.56%). Students with high confidence incorrectly determine the ratio of sides and angles that are mutually compatible. Mistakes when identifying the characteristics of a concept and recognize the conditions that determine a congruence concept of 20 students (55.56%). Students with high confidence misidentify the characteristics that are the requirements of two flat shapes can be said to be congruent. Â Keywords: Concept Mistakes, Congruence, Certainty of Response Index (CRI) Â